Differential accumulation of heavy metals in soil profile and corn and soybean grains after 15-year poultry litter application under no-tillage - Xiao, Jingxiu; Yin, Xinhua; Sykes, Virginia R.; He, Zhongqi (Journal of soils and sediments, 2022)
Purpose Heavy metal contamination in soil and crop grain due to long-term poultry litter (PL) application is largely unknown under no-till production and subtropical climate. The objective of this study was to assess the accumulation of heavy metals in soil profile and corn and soybean grains after 15-year poultry litter application under no-tillage in the Mid-south region of the United States. Materials and methods Long-term field experiments initiated in 2002 with or without PL application as a N source involving monocultures of corn and soybean under no-tillage at Milan and Spring Hill in Tennessee, USA, were selected for this study in 2017. Available and/or total contents of arsenic (As), cadmium (Cd), chromium (Cr), lead (Pb), copper (Cu), and zinc (Zn) in soil were measured in soil and corn and soybean grains. Contamination indices including contamination factor (CF), degree of contamination (DC), pollution load index (PLI), and geo-accumulation index (I geo ) were calculated. Results and discussion Long-term application of PL did not increase the total content of As, Cd, Cr, or Pb in the surface 0–15 cm soil relative to no PL application. However, total and available contents of Zn were increased by 11–17% and 2.2–5.6 times respectively, in the surface soil due to PL application. 1.7 times of total Cu and 1.7–2.1 times of available Cu were accumulated in surface soil after long-term PL application. Only total Zn content was increased by 7–17% in corn and soybean grains due to PL application. Conclusions Long-term application of PL does not pose risk of As, Pb, Cd, or Cr contamination to soil or crop grains but enhanced total and available contents of Zn and Cu in surface soil and total Zn content in crop grains under no-till production and subtropical climate. Enhanced total Zn content in corn and soybean grains is beneficial for animal and human health.